SARS‐CoV‐2 outbreak investigation in a German meat processing plant. Issue 12 (27th October 2020) - Günther, Thomas; Czech‐Sioli, Manja; Indenbirken, Daniela; Robitaille, Alexis; Tenhaken, Peter; Exner, Martin; Ottinger, Matthias; Fischer, Nicole; Grundhoff, Adam; Brinkmann, Melanie M
Abstract: We describe a multifactorial investigation of a SARS‐CoV‐2 outbreak in a large meat processing complex in Germany. Infection event timing, spatial, climate and ventilation conditions in the processing plant, sharing of living quarters and transport, and viral genome sequences were analyzed. Our results suggest that a single index case transmitted SARS‐CoV‐2 to co‐workers over distances of more than 8 m, within a confined work area in which air is constantly recirculated and cooled. Viral genome sequencing shows that all cases share a set of mutations representing a novel sub‐branch in the SARS‐CoV‐2 C20 clade. We identified the same set of mutations in samples collected in the time period between this initial infection cluster and a subsequent outbreak within the same factory, with the largest number of confirmed SARS‐CoV‐2 cases in a German meat processing facility reported so far. Our results indicate climate conditions, fresh air exchange rates, and airflow as factors that can promote efficient spread of SARS‐CoV‐2 via long distances and provide insights into possible requirements for pandemic mitigation strategies in industrial workplace settings. Synopsis: There has been considerable debate about the factors contributing to SARS‐CoV‐2 outbreaks in food processing facilities around the world. This multifactorial investigation of an outbreak in a German meat processing plant shows that transmission occurred in a confined working area over long distances. Analysis of infection event timing, spatial, climate and ventilation conditions, living quarters and transport, and viral genome sequences suggests a super spreading event that originated from a single employee. Infections among workers over a distance of 8 m from the index case suggest aerosol transmission of SARS‐CoV-2. The facilities' environmental conditions such as low temperature, low air exchange rates, and constant air recirculation, together with relatively close distance between workers and demanding physical work, may have promoted efficient aerosol transmission. In contrast to work‐related exposure, shared apartments, bedrooms, or carpools appear not to have played a major role in the initial outbreak. Viral genome sequencing reveals a characteristic set of mutations that was also observed in samples collected during a later, much larger outbreak occurring in the same processing plant. Abstract : There has been considerable debate about the factors contributing to SARS‐CoV‐2 outbreaks in food processing facilities around the world. This multifactorial investigation of an outbreak in a German meat processing plant shows that transmission occurred in a confined working area over long distances.